Impact of welding current and type of joint design on tensile properties of welded mild steel joint by using SMAW: article - Faizol, Muhamad Faiq; Abd Razak, Khalil (2018)
Oil and gas today are being developed in many sectors. Upstream, midstream and downstream. So, throughout its development, one of the major department is facilities and in facilities, basically welding play an important role for its completion. So, welding is known as sculptural process that joins materials, usually metals or thermoplastics, by causing fusion, which is distinct from lower temperature metal-joining techniques such as brazing and soldering, which do not melt the base metal. In the heavy as well as small industries, welding is widely used by metal workers in the fabrication, maintenance and repair of parts and structures. Welding current is the most influencing parameter in welding process which controls the depth of fusion; the electrode feed rate and depth of penetration. The amount of heat developed during welding depends upon the current used for a given size of electrode and filler wires. It is therefore essential that a correct current is used to produce good quality of weld and reduce the distortion problems on the job. In this study, with the objective to determine the suitable welding current in order to produce the strongest mild steel joint from two separate metals, Mild Steel plates of 6mm were welded using different joint type using Shielded Metal Arc Welding process. Single V, Double V and Square. Welding current was varied in all the cases. 100A, 110A and 120A. Mechanical properties such as ultimate tensile strength, yield strength and percentage elongation were evaluated. Results indicated that the single V joint design does have the highest Ultimate Tensile Strength in comparison to other welding joints This is due to an optimum amount of heat feed rate is given.